Marriage in Shawwal as a Socio?Religious Phenomenon: A Comparative Analysis of Islamic Norms and Customary Beliefs - Triswandani, Yogi; Kukliene, Lina; Ahyani, Hisam; Hapidin, Ahmad (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2026)
Marriage in Shawwal among Indonesian Muslim communities reflects a dialectic between normative Islamic guidance and local traditions. Some communities, such as Javanese and Madurese, recommend Shawwal weddings as reinforcement of the Prophet’s sunnah, while others, such as Minangkabau and Javanese primbon traditions, avoid them due to taboos. This study aims to explain these divergent views and clarify how religious texts and customs interact in socio?religious practice. The research employed a qualitative approach through document analysis, semi?structured interviews, participant observation, and administrative data (SIMKAH, Karanganyar Religious Affairs Office). Data were analyzed using Miles & Huberman’s interactive model to identify themes and patterns. Findings reveal that Shawwal marriages are interpreted in two ways: as recommendations reinforcing religious identity or as prohibitions affirming the binding power of custom. This synthesis demonstrates that religious practice is always negotiated between das sollen (normative Islam) and das sein (social reality). The study contributes theoretically by clarifying the interaction between Islamic texts and local traditions in shaping socio?religious practice, and practically by offering a foundation for moderate approaches that respect Islamic principles while accommodating cultural heritage. The novelty lies in its comparative lens, systematically contrasting recommendation and prohibition within the same month and linking the Indonesian case to global Scopus?indexed scholarship. [Pernikahan di bulan Syawal dalam masyarakat Muslim Indonesia memperlihatkan dialektika antara panduan normatif Islam dan tradisi lokal. Sebagian komunitas, seperti Jawa dan Madura, menganjurkan pernikahan di bulan Syawal sebagai penguatan sunnah Nabi Muhammad SAW, sementara komunitas lain, seperti Minangkabau dan tradisi primbon Jawa, menghindarinya karena dianggap tabu. Penelitian ini bertujuan menjelaskan perbedaan pandangan tersebut serta menegaskan bagaimana teks agama dan adat berinteraksi dalam praktik sosial?religius. Metode penelitian menggunakan pendekatan kualitatif dengan analisis dokumen, wawancara semi?terstruktur, observasi partisipan, dan data administratif (SIMKAH, KUA Karanganyar). Analisis dilakukan dengan model interaktif Miles & Huberman untuk mengidentifikasi tema dan pola. Hasil penelitian menunjukkan bahwa pernikahan di bulan Syawal dipahami secara beragam: sebagai anjuran yang memperkuat identitas keagamaan, atau sebagai pantangan yang menegaskan daya ikat adat. Sintesis ini menegaskan bahwa praktik keagamaan selalu dinegosiasikan antara das sollen (normatif Islam) dan das sein (realitas sosial). Kontribusi penelitian ini bersifat teoretis dengan memperjelas interaksi teks Islam dan adat dalam membentuk praktik sosial?religius, serta praktis dengan menawarkan dasar bagi pendekatan moderat yang menghormati prinsip Islam sekaligus mengakomodasi tradisi lokal. Kebaruan penelitian terletak pada lensa komparatif yang secara sistematis mengontraskan anjuran dan pantangan dalam bulan yang sama, serta mengaitkannya dengan literatur global berstandar Scopus.]